Hurricane Camille : monster storm of the Gulf Coast - Hearn, Philip D. (University Press of Mississippi, 2004)
On August 17, 1969, Hurricane Camille roared out of the Gulf of Mexico and smashed into Mississippi's twenty-six miles of coastline. Winds were clocked at more than 200 miles per hour, tidal waves surged to nearly 35 feet, and the barometric pressure of 26.85 inches neared an all-time low. Survivors of the killer storm date events as BC and AC--Before Camille and After Camille. The history of Hurricane Camille is told here through the eyes and the memories of those who survived the traumatic winds and tides.